Novel structured diacylglycerol (DAG) rich oleo formulations activate the Nrf2 pathway and impedes NF-κB translocation to mitigate pre-clinical conditions of hypertension. (January 2020) - Das, Kankana; Kundu, Amit; Karmakar, Sanmoy; Ghosh, Mahua
Graphical abstract: Highlights: Study establishes central and peripheral mechanisms involved in hypertension. DAG oil rich in Capric acid and Caprylic acid activates Nrf2/Mn-SOD pathway. DAG oil rich in Capric acid and Caprylic acid inhibits ROS/NF-κB pathway. DAG comprising Caprylic acid is better than Capric acid in mitigating hypertension. Abstract: The objective of the present work was to assess the ameliorative potential of two novel edible diacylglycerol oil-formulations comprising caprylic acid, C8:0 or capric acid, C10:0 in treating CdCl2 induced in vivo hypertension at molecular level. Male Wistar rats were randomly divided into 4 groups (1) control; (2) DAG oil-treated group (2 gm/day DAG oil); (3) hypertensive group (1.0 mg/kg of CdCl2 for 2 weeks, i. p); and (4) hypertensive/DAG oil-treated group (2 gm/day DAG oil) (14 days). Hematological, biochemical and molecular parametric tools were performed to evaluate the protective efficacy of DAG oils against CdCl2 -induced hypertension. Systolic blood pressure (SBP) measured non-invasively using BIOPAC-MP36 system (BIOPAC System Inc., USA). It was found that the pretreatment of DAG oil provided a significant improvement in renal antioxidant status, reduced the lipid peroxidation and the levels of inflammatory markers that were aggravated due to induced CdCl2 -toxicity. Further, results of protein expression showed that DAG oil pretreatment normalized the renal expression of Nrf2/Keap1 and its downstream regulatory proteins in CdCl2 -treated rat kidney. DAG oils also effectively attenuated CdCl2 -induced renal apoptosis by the up-regulation of anti-apoptotic proteins such as Bcl-2 and down-regulation of Bax, caspase-3, caspase-9 and Cytochrome c . Histological and immunohistochemical observations provided further evidence that the DAG oils effectively protected the kidney from CdCl2 -mediated oxidative damage. The results suggest that DAG oils ameliorated CdCl2 -induced oxidative renal injury by activating the Nrf2/Mn-SOD pathway and inhibiting the ROS/NF-κB pathway. Evidences have revealed that Cy-DAG exhibited better efficacy than the Cp-DAG against induced hypertensive conditions.